Peningkatan Bumdes Berdasarkan Aspek Metodologi Melalui PKM - Falimu, Falimu; Aimang, Hasrat A; Lamadang, Karmila P (Penerbit Goodwood, 2023)
Purpose: The purpose of establishing BUMDesa is regulated in the Village Head Regulation, Regulation of the Minister of Villages, Development of Disadvantaged Regions, and Transmigration of the Republic of Indonesia Number 4 of 2015 concerning the Establishment, Management, and Dissolution of BUMDes. Village-owned enterprises were established with the aim of accommodating all economic activities, public services handled by the village, and/or collaboration between villages. The aim of BUMDes is to enable long-term economic improvement in rural areas. Methodology/approach: The stages of community service activities begin with outreach to the target community in Lauwon village, East Luwuk District. The method of implementing the activity is the socialization of BUMDes organizational management and BUMDes management training. Results/findings: As managers and members of BUMDes in villages, the community has an important role in the growth and progress of its economy through BUMDes. The problem that occurs is that the BUMDes established in Lauwon Village are not developing well. There are many factors that cause this, including irregular management of the BUMDes organization and inconsistent management and administration, as well as a lack of understanding of the BUMDes management itself, so that the village's potential is difficult to implement. Lauwon Village is one of the villages in the East Luwuk District, Banggai Regency, which has a BUMDes, but the management is not in accordance with the expectations of the village government and the community. This is due to the integrity of institutional management, as well as the absence of Articles of Association (AD) and Bylaws (ART), infrastructure, and no mapping of village potential. Contribution: This service is expected to improve the ability of village officials to manage business entities owned by the village. Limitation: Focuses on maximizing financial profits and improving the welfare of village communities